PET/CT images of a patient with haemophagocytic lymphohistiocytosis - Koç, Zehra Pnar; Akarsu, Saadet; Balci, Tansel; Unal, Kemal (BMJ Publishing Group, 2012)
Haemophagocytic lymphohistiocytosis (HLH) is a rare immune disorder that predominantly affects macrophages and T lymphocytes and leads to multiple organ disease and death. The characteristic pathological finding in the bone marrow and the other affected tissues is haemophagocytosis of macrophages (macrophages digesting erythrocyte). Primary (hereditary) and secondary (acquired) forms of the disease are present. A patient with documented HLH disease revealed by positron emission tomography/CT is reported in this paper. Copyright 2012 BMJ Publishing Group. All rights reserved.
Keywords: cyclosporin; dexamethasone; etoposide; ferritin; methotrexate; steroid; Acinetobacter baumannii; adolescent; anemia; article; bacterium identification; bone marrow biopsy; cardiomegaly; case report; computer assisted emission tomography; family history; ferritin blood level; fever; hemophagocytic lymphohistiocytosis; hepatomegaly; human; human tissue; laboratory test; leukocytosis; liver disease; male; neutrophil count; physical examination; pleura effusion; priority journal; rash; sedimentation rate; sore throat; thorax radiography; treatment response